AN EVALUATORY STUDY OF A ROCHA KENYA’S CHRISTIAN APPROACH IN CONSERVATION OF NATURE IN KILIFI COUNTY - Nyale, Mercy Chizi; Chidongo, Dr. TsaweMunga wa; Joshua, Professor Stephen Muoki (Journal of Philosophy, Culture and Religion, 2019)
Purpose: Despite the efforts ARK has put in place with regard to environmental conservation, Kilifi County still faces a lot of environmental degradation resulting from stone cutting and sand harvesting which renders several hectares of land scarred with pits and devoid of vegetation cover. The study focused on the input of Christianity on nature conservation in this county. Methodology: The study employed qualitative methodology to acquire primary data. Purposive, convenience, homogenous and snowballing sampling techniques were used to identify respondents for interviews and focus group discussions. The study also utilized documentary analysis which was done by analyzing ARK's publications like brochures, newsletters, magazines and even minutes from seminars to establish the organization's environmental conservation in depth. Guided by the objectives, the raw data was collated and arranged thematically. Findings: It was realized in the study that deforestation, quarrying and sand harvesting were the major forms of environmental degradation in Watamu and Marafa which has led to vulnerability of wild animals and birds and a scarcity of medicinal herbs. The major contributing factors towards this environmental degradation were poverty and population increase, development and ignorance. Further, it was established that care for creation and environmental stewardship are the Christian obligations towards nature. As a response towards environmental degradation, Christian communities in Watamu have established employment opportunities to curb the environmental degradation menace. Unique Contribution to Theory, Practice and Policy: There is need to create more awareness on the importance of forest and its resources so as to create a positive attitude towards its conservation. Again there is need to train people to embrace proper farming methods like FGW done by ARK.